Hybrid herpes simplex virus/Epstein-Barr virus amplicon viral vectors confer enhanced transgene expression in primary human tumors and human bone marrow-derived mesenchymal stem cells - Sia, Kian Chuan; Chong, Wei Kin; Ho, Ivy A. W.; Yulyana, Yulyana; Endaya, Berwini; Huynh, Hung; Lam, Paula Y. P. (The journal of gene medicine, 2010)
Background Herpes simplex virus type‐1 (HSV‐1) amplicon vectors are attractive tools for gene transfer because of their large DNA insert capacity, their broad host range of vector transduction and a minimal immune response as a result of the absence of helper viruses during viral packaging. However, the transient gene expression remains a challenge for the translation of HSV‐1 amplicon based therapeutic strategies to a clinical setting. Although oriP/EBV nuclear antigen (EBNA)‐1 elements of Epstein–Barr virus (EBV) have been successfully employed to achieve prolonged transgene expression, little is known about the stability of the EBNA‐1 elements in the context of HSV‐1 amplicon viral vectors. Methods We have generated HSV/EBV hybrid vectors expressing the mutant EBNA‐1 gene with the luciferase reporter gene bicistronically to enable monitoring of EBNA‐1 expression in real‐time, both in vitro and in vivo. Results The results obtained showed that the HSV/EBV hybrid vectors could mediate high levels of transgene expression (ranging from approximately two‐fold to nine‐fold) in primary human tumor cells and human bone marrow‐derived mesenchymal stem cells compared to the control vector. Prolonged transgene expression could also be observed in primary patient‐derived human hepatocellular carcinoma xenografts and in the mouse brain parenchyma up to a period of 17 and 365 days, respectively. Conclusions Taken together, we have demonstrated that these hybrid vectors could be promising tools as carriers of therapeutic genes in mesenchymal stem cells or even provide an alternative non‐integrating platform for the generation of induced pluripotent stem cells. Copyright © 2010 John Wiley & Sons, Ltd.